Effects of Motivational Interviewing and Wearable Fitness Trackers on Motivation and Physical Activity: A Systematic Review. Issue 2 (February 2021) - Nuss, Kayla; Moore, Kristen; Nelson, Tracy; Li, Kaigang
Objective: To systematically review the impacts of Wearable Fitness Trackers (WFTs), Motivational Interviewing (MI), and Self Determination Theory (SDT)–based interventions on physical activity (PA) and motivation for PA. Data Source: Manuscripts published between 2008 and 2018 in PubMed, Web of Science, CABAbstracts, and SPORTDiscus database were reviewed. Study Inclusion and Exclusion Criteria: Inclusion criteria were original pilot studies, randomized controlled trials (RCT), cross-sectional studies, qualitative assessments, prospective cohort studies, longitudinal observational studies, and pretest posttest designs published in peer-reviewed journals. Data Extraction: Studies were evaluated by 2 independent researchers for inclusion. Data Synthesis: Extracted data were synthesized in a tabular format and narrative summary. Results: Twenty-six studies met final inclusion criteria, 10 addressed WFT use and PA behavior, 4 investigated WFT use and its association with motivation for PA, and 10 examined SDT and/or MI and their effect on motivation for PA and/or PA behavior. Finally, 2 studies addressed SDT-based MI, WFT use, and the combined effect on PA behavior. Conclusions: While SDT-based interventions and MI positively impact motivation for PA and PA behavior, WFTs revealed mixed results. Wearable Fitness Trackers prove effective among individuals not currently meeting PA guidelines but have little impact on other populations. Self Determination Theory, MI, and WFTs use provides a promising combination of interventions to increase PA among sedentary individuals, though research is limited.